Jomlo sampai Halal: Refleksi Sosiologis Budaya Generasi Milenial pada Mahasiswa Jomlo di IAIN Pontianak - Khairunnisyah, Khairunnisyah; Prasojo, Zaenuddin Hudi (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2019)
The article is based on the fact that â€œjomloâ€ or being single has become a new trend as a sociological phenoÂmenon and the product of the practice of hijrah within the life of Muslim youth, especially Indonesian Muslim students. The concept of dating for those who practice the